Model Rapid Application In Development Information Systems Population Data Processing (Case Study : Tambusai District Office In The Kabupaten Rokan Hulu Riau ) - Ramadhan, Muhammad Sabir; Aswati, Safrian; *, Iskandar (IJRDO -Journal of Computer Science Engineering, 2017)
Tambusai district office in the Kabupaten Rokan Hulu Riau Province is an instance that is currently resident in terms of data processing that is processed by computerization. But still using an application program such as Microsoft Word that affect some of the problems that is inaccurate population data information contained in these districts and population data duplication because absence of the key (key) to prevent duplication. In this case the data are processed population is active population data, population data and population data moved has died. It takes an information system to anticipate the issues mentioned above. The information system is designed to implement the model of Rapid Application Development (RAD) where in generating the information system for processing data on population at the District Office Tambusai the regency of Rokan Hulu, Riau Province through a number of phases, beginning with the planning phase requirement needs of the system, involving users to design and build system (the activity is performed repeatedly to reach a mutual agreement), and the last stage of implementation.